THE ERRORS IN SOLVING GEOMETRY QUESTIONS ON CONGRUENCE AND SIMILARITY TOPICS BY FLORENCE LITTAUER MIXED PERSONALITY TYPE STUDENTS - Hariyanto, Nanang Hadi; Purwanto, Purwanto; Kusumasari, Vita (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to describe errors and determine the factors that cause errors in solving geometry problems in terms of students' mixed Florence Littauer personality types. This research is qualitative descriptive research. The subjects of this research were ninth-grade students at SMPN 13 Malang who had been given material on